2021
DOI: 10.4103/jfmpc.jfmpc_2037_20
|View full text |Cite
|
Sign up to set email alerts
|

An update on the diagnostic biomarkers for asthma

Abstract: Asthma is a respiratory disorder accounts for ~339 million cases per annum. The initial diagnosis of asthma relies on the symptomatic identification of characters, such as wheeze, shortness of breath, chest tightness, and cough. The presence of two or more of these symptoms may be considered as indicative of asthma. The asthma-diagnostic also involves spirometry test before and after inhaling a bronchodilator like albuterol. Because asthma pathophysiology involves participation of immune system, the cytokines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 132 publications
(167 reference statements)
0
7
0
Order By: Relevance
“…Similarly, the supernatants obtained from the processed sputum are used in evaluating molecular markers of airway inflammation such as eosinophil cationic protein (ECP), eosinophil-derived neurotoxin, and major basic protein for eosinophil activation, tryptase for mast cell activation, and cytokine production (e.g., IL-5) as well as albumin and fibrinogen that are useful markers of microvascular leakage ( 6 , 8 ). The levels of these molecular markers were raised in the processed sputum from asthmatic patients than from control subjects ( 3 , 6 , 33 35 ).…”
Section: Applications Of Induced Sputummentioning
confidence: 93%
See 2 more Smart Citations
“…Similarly, the supernatants obtained from the processed sputum are used in evaluating molecular markers of airway inflammation such as eosinophil cationic protein (ECP), eosinophil-derived neurotoxin, and major basic protein for eosinophil activation, tryptase for mast cell activation, and cytokine production (e.g., IL-5) as well as albumin and fibrinogen that are useful markers of microvascular leakage ( 6 , 8 ). The levels of these molecular markers were raised in the processed sputum from asthmatic patients than from control subjects ( 3 , 6 , 33 35 ).…”
Section: Applications Of Induced Sputummentioning
confidence: 93%
“…Similarly, the supernatants obtained from the processed sputum are used in evaluating molecular markers of airway inflammation such as eosinophil cationic protein (ECP), eosinophil-derived neurotoxin, and major basic protein for eosinophil activation, tryptase for mast cell activation, and cytokine production (e.g., IL-5) as well as albumin and fibrinogen that are useful markers of microvascular leakage (6,8). The levels of these molecular markers were raised in the processed sputum from asthmatic patients than from control subjects (3,6,(33)(34)(35). Correspondingly, Eltboli and Brightling (36) showed that in COPD patients, induced sputum can be used to assess airway inflammation for individuals suffering from the disease by performing differential cell counts and therefore allowing for a more tailored treatment and management and in diagnosing chronic lung diseases.…”
Section: Applications Of Induced Sputummentioning
confidence: 99%
See 1 more Smart Citation
“…IL-13 is an important cytokine in airway hyper responsiveness, mucus production and various immune reactions. IL-13t can be detected in serum 46 . TNF is proinflammatory cytokine implicated in modulation of inflammation.…”
Section: Mutated Targets With Loss Of Function Variants Receptor Tyro...mentioning
confidence: 99%
“…Elevated frequencies of Th2 cells in the airways release specific cytokines that control the rebound of allergic inflammation, including IL-4 13 . In addition, IL-4 is very important in driving the differentiation of helper T lymphocyte precursors into Th2 response cells 14 .…”
Section: /22mentioning
confidence: 99%